Hybrid Nanomaterials Flexible Electronics Materials - Vargas-Bernal, Rafael; He, Peng; Zhang, Shuye (IntechOpen, 2020)
Two of the hottest research topics today are hybrid nanomaterials and flexible electronics. As such, this book covers both topics with chapters written by experts from across the globe. Chapters address hybrid nanomaterials, electronic transport in black phosphorus, three-dimensional nanocarbon hybrids, hybrid ion exchangers, pressure-sensitive adhesives for flexible electronics, simulation and modeling of transistors, smart manufacturing technologies, and inorganic semiconductors.